A Case Report Snake Bite Induced Acute Kidney Injury (AKI) - MD, Abbas SK; A, Noorjahan; Reddy, C. Bhargav; K, Mallikarjuna; Saivani, Y (Journal of Pharmacy Practice and Community Medicine)
Acute Kidney Injury (AKI) complicating snake envenomation may pass for a “neglected” health condition in regions or parts of the world where its incidence is not as common. Now -a – days snake bite is a quite common in rural areas of India. Hence snake bite is considered as a important health hazard. Snake bite may also cause the mortality and morbidities of a person. Snake bite may produce the toxic effects to the multiple organs and may produce the injury mainly to the kidneys. Mostly snake bite produce the acute kidney injury and also risk for the many complications to the multiple organ dysfunctions and if it was not treated well leads to the mortality. Here we report a case of a person with snake bite which induce the acute kidney injury i,e acute tubular necrosis. He was treated with appropriate therapy according to the symptoms and also treated with haemodialysis without development of adverse effects and with supportive therapy.
Keywords: Snake bite; acute kidney injury; Acute tubular necrosis; Supportive therapy; Maintained Haemodialysis (MHD)